The impact of political identity, grouping, and discussion on young people's views of political documentaries. Issue 4 (2nd October 2018) - Stoddard, Jeremy; Chen, Jason
ABSTRACT: This study focuses on how young people read and discuss two political documentary films, Labor Day and Hillary: The Movie . We were specifically interested in the impact of the film viewing and discussion on participants' beliefs about the issues in the films, how they view evidence and expertise in the films, and how the session impacted their views of documentaries as a source. Groups were designed according to composite political scores and individuals ( n = 30) were selected to form liberal, conservative, and two mixed groups (strong and moderate) for the viewing and discussion. Our analysis illustrates the power of political ideology in shaping how expertise is viewed and how evidence is warranted in film – and the role of social context and peer discussion in this process. Implications for media and democratic education in times of political polarization are discussed.